Distributed generation systems design, operation and grid integration - Gharehpetian, G. B.; Mousavi Agah, S. Mohammad (Butterworth-Heinemann, 2017)
Distributed Generation Systems: Design, Operation and Grid Integration closes the information gap between recent research on distributed generation and industrial plants, and provides solutions to their practical problems and limitations. It provides a clear picture of operation principles of distributed generation units, not only focusing on the power system perspective but targeting a specific need of the research community. This book is a useful reference for practitioners, featuring worked examples and figures on principal types of distributed generation with an emphasis on real-world examples, simulations, and illustrations. The book uses practical exercises relating to the concepts of operating and integrating DG units to distribution networks, and helps engineers accurately design systems and reduce maintenance costs.--Provided by publisher.